Realizing Pancasila Student Profiles in the Elementary School with Learning Media Based on Local Wisdom ’Barongan Masks’ - Srirahmawati, Anjar; Hunaifi, Abdul Aziz (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2022)
These research objectives were to examine the values of the Pancasila student profile contained in the use of the barongan mask media and to analyze the effectiveness of the Barongan mask art craft to realize the Pancasila student profile in elementary schools. The research method was a descriptive method with a qualitative approach. The research subjects consisted of 28 students, three teachers, and the headmaster principal at State Elementary School 1 of Kalikejambon, Tembelang Sub-district, Jombang Regency. Three data collection techniques were used in this research, including literature study, observation of the research location, and interviews. Meanwhile, the technical analysis of the data went through three stages, namely data reduction or summarizing important things obtained during the research, presenting data in narrative or tabular form, and drawing conclusions. The research results indicated that: (1) the barongan mask art craft media had values that matched the profile of Pancasila students; and (2) the barongan mask art craft media was considered effective to be used to realize the Pancasila student profile in elementary schools, as evidenced by the achievement of each profile element of Pancasila students (who were faith and feared of God Almighty and had a noble character, global diversity, cooperation, independence, critical reasoning, and creativity). Most of the characters that appeared in school activities were under the key element indicators in each element of the Pancasila student profile.